2011
DOI: 10.1089/dia.2010.0204
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Pharmacokinetics of Intradermal Insulin Administered Using Microneedles in Type 1 Diabetes Subjects

Abstract: Background: This study compared the pharmacokinetics, postprandial glycemic response, and pain associated with intradermal lispro insulin delivery using a microneedle with that of a conventional catheter. Subjects and Methods: Five subjects with type 1 diabetes were administered a bolus infusion of lispro insulin using a 9-mm-long subcutaneous catheter (control treatment) and a 0.9-mm-long microneedle (study treatment), followed by consumption of a standardized meal. Blood samples were periodically assayed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 21 publications
4
71
1
7
Order By: Relevance
“…The phase 2 study even suggested that microneedles could provide 552 a better plasma profile than subcutaneous injection because of faster absorption. In accordance with these findings, Prausnitz and colleagues have shown that microinjections of insulin with hollow microneedles into the depth of 0.9-1 mm induced a faster onset of insulin action than subcutaneous injections (Gupta et al, 2009(Gupta et al, , 2011Norman et al, 2013). This result suggests that the microneedle injection of insulin is delivered to the papillary dermal region, which has rich capillary and lymphatic networks, allowing faster absorption than after subcutaneous injection.…”
Section: A Development Challenges Of Peptide Delivery Formulationsmentioning
confidence: 74%
“…The phase 2 study even suggested that microneedles could provide 552 a better plasma profile than subcutaneous injection because of faster absorption. In accordance with these findings, Prausnitz and colleagues have shown that microinjections of insulin with hollow microneedles into the depth of 0.9-1 mm induced a faster onset of insulin action than subcutaneous injections (Gupta et al, 2009(Gupta et al, , 2011Norman et al, 2013). This result suggests that the microneedle injection of insulin is delivered to the papillary dermal region, which has rich capillary and lymphatic networks, allowing faster absorption than after subcutaneous injection.…”
Section: A Development Challenges Of Peptide Delivery Formulationsmentioning
confidence: 74%
“…The group observed a 66%-77% drop in BGL in 4-6 h. [61] Hollow microneedles used by Prausnitz and co-workers to deliver insulin lispro intradermally, showed peak plasma concentration at around half the time compared to subcutaneous catheter infusion and higher blood glucose lowering efficacy in type 1 diabetic patients. [62] Apart from physical enhancers, chemical permeation enhancers can also improve transdermal delivery of macromolecules. For example, ethanol increased transdermal delivery of thyrotropin-releasing hormone analog by twofold while skin penetrating peptides coadministered with unfractionated heparin increased protein flux by 24-to 36-fold compared to protein alone.…”
Section: Wwwadvhealthmatdementioning
confidence: 99%
“…Blood glucose levels were lower with ID insulin delivery than with SC delivery but of uncertain statistical significance. 29 Another option for applying insulin into a compartment that allows more rapid insulin absorption is the intraperitoneal route. The Swiss/German company Roche Diagnostics has a redesigned system in a late stage of development that is supposed to allow safe and efficient insulin application into this compartment by means of a special catheter (DiaPort).…”
Section: Intradermal Application Of the Insulinmentioning
confidence: 99%